The effect of non-surgical periodontal therapy on peroxidase activity in diabetic patients: a case-control pilot study - Goncalves, Daniela; Bello Correa, Fernanda Oliveira; Khalil, Najeh Maissar; Mascarenhas de Faria Oliveira, Olga Maria [UNESP]; Perez Orrico, Silvana Regina [UNESP] (Wiley-Blackwell, 2008)
Objective: To evaluate the effect of periodontal therapy on clinical parameters as well as on total salivary peroxidase (TSP) activity and myeloperoxidase (MPO) activity in the gingival crevicular fluid (GCF) of patients with type 2 diabetes mellitus (DM2) and of systemically healthy individuals.Material and Methods: Twenty DM2 subjects with inadequate metabolic control (test group) and 20 systemically healthy individuals (control group), both groups with chronic periodontitis, were enrolled. Periodontal clinical parameters, namely periodontal probing depth (PD), clinical attachment level (CAL), visible plaque index (VPI), bleeding on probing (BOP), gingival bleeding index (GBI) and presence of suppuration (SUP), as well as TSP activity and GCF MPO activity, were assessed before and 3 months after non-surgical periodontal therapy.Results: At baseline and 3 months post-treatment, the test group presented a higher percentage of sites with VPI and BOP (p < 0.01). MPO activity in the GCF presented lower values (p < 0.05) for the test group at both baseline and the post-treatment period. The periodontal treatment resulted in a significant improvement of most clinical and enzymatic parameters for both groups (p < 0.05).Conclusions: In both groups, the periodontal therapy was effective in improving most clinical parameters and in reducing salivary and GCF enzymatic activity. The diabetic individuals presented lower MPO activity in the GCF.
Keywords: diabetes mellitus; glycaemic control; myeloperoxidase; salivary peroxidase; periodontal disease/therapy